Une critique souterraine : le Prix du roman jeunesse - Florence Gaiotti; Guillemette Tison (Strenae)
This study, based on a selection committee’s reading notes about anonymous manuscripts of candidates for the Prix du roman jeunesse, awarded from 1989 to 2003 by the French Ministry of Youth and Sports, and held at the archives at the CRILJ (Centre de recherche et d'information sur la littérature de jeunesse), identifies an unusual aspect of criticism: an "underground" reviewing in which readers are free to express themselves uninhibitedly on positive and negative aspects of the submitted works, since their notes were not intended to be disclosed.